Antibacterial Activity of Freshwater Microalga Scenedesmus sp. on Foodborne Pathogens Staphylococcus aureus and Salmonella sp. - Ishaq, Aisha Gogoba; Matias-Peralta, Hazel Monica; Basri, Hatijah; Muhammad, Muhammad Nmaya (Journal of Science and Technology, 2016)
Microalgae possess promising bioactive compounds with a wide range of activities. In this study, crude pigment extract of Scenedesmus sp. a freshwater microalga was screened against two known foodborne pathogens Staphylococcus aureus (ATCC 25923) and Salmonella sp. (ATCC 14028) to evaluate its antimicrobial properties. The crude pigment of the microalga was extracted with 90 % acetone whereas antibacterial screening was done by agar well diffusion method. In addition, the MIC of crude pigment was determined following the macrobroth dilution method. Concentrations ranging from 0.35mg/ml – 3.48 mg/ml demonstrated highest inhibitory activity against Staphylococcus aureus (ATCC 25923).  The MIC was achieved at 0.08 mg/ ml. On the other hand, there was no inhibitory activity at any concentration of crude extract against Salmonella sp. (ATCC 14028).  Results of this study suggest that the inhibitory activity may be limited to gram positive foodborne pathogen Staphylococcus aureus.